2018
DOI: 10.1155/2018/1402674
|View full text |Cite
|
Sign up to set email alerts
|

Levels and Health Risk Assessment of Heavy Metals in Soil, Water, and Vegetables of Dar es Salaam, Tanzania

Abstract: This study assesses heavy metals' levels in water, soil, and vegetables (Ipomoea batatas (Matembele), Amaranthus hybridus (Mchicha), Abelmoschus esculentus (Bamia), and Solanum melongena (Bilinganya)) from the Chang' ombe police garden located in Temeke district, Tanzania. Also, it examines potential health risks from consumption of the vegetables. The samples of soils, water, and vegetables were randomly collected, processed, and analyzed for heavy metals using Atomic Absorption Spectrophotometry. The heavy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(84 citation statements)
references
References 33 publications
1
80
2
1
Order By: Relevance
“…The metal concentrations in the leafy vegetables were slightly higher than fruit vegetables could probably be ascribed to its high foliar surface area and industrial activities. Some common vegetables including Amaranthus species are proficient of accuring high heavy metals levels from contaminated irrigating water or growing soil as reported earlier (Kacholi and Sahu, 2018). These findings suggests that many contaminated vegetables are sold in Kawran Bazar city market (Dhaka, Bangladesh) which are not safe for human consumption.…”
Section: Table IV Comparison Of Other Reports Of Metal Concentrationmentioning
confidence: 55%
See 3 more Smart Citations
“…The metal concentrations in the leafy vegetables were slightly higher than fruit vegetables could probably be ascribed to its high foliar surface area and industrial activities. Some common vegetables including Amaranthus species are proficient of accuring high heavy metals levels from contaminated irrigating water or growing soil as reported earlier (Kacholi and Sahu, 2018). These findings suggests that many contaminated vegetables are sold in Kawran Bazar city market (Dhaka, Bangladesh) which are not safe for human consumption.…”
Section: Table IV Comparison Of Other Reports Of Metal Concentrationmentioning
confidence: 55%
“…The Cr toxicity affects many organs in humans, such as liver, kidney, lungs and spleen, causing severe biochemical defects and cancer. High Average Daily Intake (ADI) of heavy metals has been also reported in Bangladesh (Kacholi and Sahu, 2018).…”
Section: Average Daily Intake (Adi) Of Heavy Metalsmentioning
confidence: 98%
See 2 more Smart Citations
“…Research has shown that high concentrations of Cd and Pb in the soil have led to higher concentrations of these metals in mushrooms growing on such soils . Essential elements including Zn, Cu and Fe play a significant role in the physiology of plants and animals as long as they are within the recommended limits, but metals such as Pb, Cd, Cr and Hg are toxic environmental pollutants that pose health risks. Significantly lower concentrations of metals have been detected in A. biosporus , Polyporus frondosis and Armillariella mellea despite these mushrooms growing in highly polluted soils .…”
Section: Introductionmentioning
confidence: 99%